Inquisitive Understanding of Samprapti Vighatana in Primary Hypothyroidism with Obesity as a Rasapradoshaja Vikara - Shruthi Shivarama; Mythrey RC (RGUHS Journal of AYUSH Sciences, 2025)
The thyroid gland is an essential endocrine gland which plays anbsp significantrole in chemical reactions in the body maintaining basal metabolic rate as well as growth and development. It is located in the neck region where Vishuddha chakra resides. Primary hypothyroidism ornbsp overtnbsp hypothyroidism is a condition where there is elevated thyroid stimulating hormone TSH gt10 mUL with free T4 level below the normal range exhibiting features like weight gain dry skin cold intolerance depression etc. Aharaja Viharaja Manasika and Jatajanya nidanas are act as a moola karana in vyadhi utpatti. This makes Kapha Vata vruddhi and Pitta kshayanbsp leading to Agni vaishamyata Jatharagni Rasa and Medho dhatvagni vyatyasa causing primary hypothyroidism with obesity. Ayurveda Chikitsa focuses on Nidana parivarjana Samshodhana Samshamana and proper implementation ofnbsp Dinacharya and Pathya Apathya. This eventually increases Agni bala balances the tridosha and manages the Rasa and Medo dhatu functions and helps in manage the Vyadhi. Thenbsp prognosis ofnbsp thenbsp disease has a broader impact on another system like the respiratory cardiac gastrointestinal metabolic skin renal and musculoskeletal systems exhibiting various clinical features. Reviewing the literature it was found that Primary hypothyroidism and obesity have an intriguing link. Hence it is the need of the hour and an attempt is made to strategically interpret and analyse the concepts for proper management.